Cover Feature: Two‐Dimensional NiO@C‐N Nanosheets Composite as a Superior Low‐Temperature Anode Material for Advanced Lithium‐/Sodium‐Ion Batteries (ChemElectroChem 17/2020). Issue 17 (12th August 2020) - Bai, Zhengyu; Lv, Xiao; Liu, Dai‐Huo; Dai, Dongmei; Gu, Jiali; Yang, Lin; Chen, Zhongwei
Abstract : The Cover Feature depicts a superior low‐temperature lithium‐/sodium‐ion battery with a two‐dimensional NiO@C−N nanosheet anode. The prepared NiO@C−N anode material exhibits superior Li/Na storage performances over a wide temperature range from 25 °C to −40 °C, and its electrode kinetics can be enhanced by optimizing the electrolyte and engineering the anode. More information can be found in the Article by Z. Bai, X. Lv et al .